2020
DOI: 10.3390/cells9102287
|View full text |Cite
|
Sign up to set email alerts
|

Targeting DNA Repair, Cell Cycle, and Tumor Microenvironment in B Cell Lymphoma

Abstract: The DNA double-strand break (DSB) is the most cytotoxic lesion and compromises genome stability. In an attempt to efficiently repair DSBs, cells activate ATM kinase, which orchestrates the DNA damage response (DDR) by activating cell cycle checkpoints and initiating DSB repair pathways. In physiological B cell development, however, programmed DSBs are generated as intermediates for effective immune responses and the maintenance of genomic integrity. Disturbances of these pathways are at the heart of B cell lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 99 publications
1
14
0
Order By: Relevance
“…Also, targeting cytotoxic T-lymphocyte-associated protein 4 (CTLA-4), PARPi combined with anti-CTLA-4 antibodies has demonstrated similar effects [ 127 , 128 ]. Apart from immune checkpoint blockade therapy, chimeric antigen receptor T cell (CAR-T) immunotherapy has not been applied to solid tumors.…”
Section: The Effect Of Altered Ddr Pathway Interactions On Icismentioning
confidence: 99%
See 1 more Smart Citation
“…Also, targeting cytotoxic T-lymphocyte-associated protein 4 (CTLA-4), PARPi combined with anti-CTLA-4 antibodies has demonstrated similar effects [ 127 , 128 ]. Apart from immune checkpoint blockade therapy, chimeric antigen receptor T cell (CAR-T) immunotherapy has not been applied to solid tumors.…”
Section: The Effect Of Altered Ddr Pathway Interactions On Icismentioning
confidence: 99%
“…Aging-related secretory phenotypes function to recruit innate immune cells, including NK cells and macrophages, as well as CD8 + T cells [127]. Instability of aneuploid accumulation after chromosome separation into the micronucleus can directly up-regulate senescence-associated secretory phenotypes (SASP) [189][190][191].…”
Section: Innate Immune Cellmentioning
confidence: 99%
“…The effect of anti-cancer agents on cell-cycle progression is important. Most, if not all, human cancer types show a deregulated control of G1 progression, a period in which cells decide whether to begin proliferation or stay quiescent [ 46 ]. In the cell-cycle analysis, we observed that CH-AuNPs did not induce cell-cycle alterations in HUVECs, similar to our observations in tumor (HeLa and MCF-7) [ 17 ] and leukemic (K562 and CEM) [ 18 ] cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The ATM gene encodes a protein that is an important cell cycle checkpoint kinase that phosphorylates important sites such as CHK2, p53, MRN complex and plays a prominent role in the HR pathway ( 83 ). ATM, an important factor in DNA damage repair, signals in association with PARP-1 to activate E3 ubiquitin ligase within one hour of recognition of a DNA double-strand break.…”
Section: Targeted Dna Damage Repair To Explore Immunotherapy Biomarkermentioning
confidence: 99%
“…The ATM gene encodes a protein that is an important cell cycle checkpoint kinase that phosphorylates important sites such as CHK2, p53, MRN complex and plays a prominent role in the HR pathway (83) and in this way enhance the effect of ICI treatment. Therefore, mutations in ATM can be used to predict the clinical efficacy of ICI as an ICI therapeutic target and biomarker (87).…”
Section: Atmmentioning
confidence: 99%